PELATIHAN PEMBUATAN ARUS KAS UNTUK UMKM WARUNG BAMBU OMAH - Nurmadewi, Dita; Cahyaningsih , Elin (LPPM Universitas Bina Bangsa, 2025)
This project focuses on conducting cash flow management training for the SME Warung Bambu Omah, aimed at enhancing the financial skills and knowledge of the SME owner. Micro, small, and medium enterprises (SMEs) hold a crucial role in Indonesia's economy but often encounter challenges in managing their finances effectively. Through training that utilizes Google Spreadsheet, it is hoped that SMEs can better manage their finances and enhance their operational stability. This service activity employs observation and direct training methods, where the owner of Warung Bambu Omah is trained to organize and utilize cash flow using this digital tool. The results of this activity show an improvement in understanding and skills in financial management, as well as the potential for using technology to support the sustainability of SME businesses.